2010
DOI: 10.1088/0031-9155/55/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-field photon dose following removal of the flattening filter from a medical accelerator

Abstract: The aim of this paper is to determine the effect of removing the flattening filter from a linear accelerator on the out-of-field photon dose. A Monte Carlo model was used to simulate 6 MV and 18 MV photon beams from a Varian 2100 accelerator with the flattening filter in place and with it removed. The out-of-field photon doses and composition (head leakage, patient scatter and collimator scatter) were calculated from square open fields in a water tank as a function of distance from central axis, field size and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
124
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(137 citation statements)
references
References 37 publications
10
124
1
2
Order By: Relevance
“…In order to gain a better understanding of the source of TPS calculation inaccuracies, the accuracy of each individual component of peripheral dose was evaluated, paralleling the methodology described by Kase et al ( 1 ) and Kry et al ( 20 ) The total dose outside of the treatment field T was thereby decomposed into leakage radiation L , scatter from collimators and other beam line components C , and patient scatter P : T=L+C+P …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain a better understanding of the source of TPS calculation inaccuracies, the accuracy of each individual component of peripheral dose was evaluated, paralleling the methodology described by Kase et al ( 1 ) and Kry et al ( 20 ) The total dose outside of the treatment field T was thereby decomposed into leakage radiation L , scatter from collimators and other beam line components C , and patient scatter P : T=L+C+P …”
Section: Methodsmentioning
confidence: 99%
“…These results from Pinnacle were then compared to previously published Monte Carlo results simulated with a detailed model of a Varian 2100 Clinac, the same experimental setup conditions, and a parallel computational approach. ( 20 ) …”
Section: Methodsmentioning
confidence: 99%
“…The desktop software, the hardware of the linac, and the TPS influence the treatment time. Kry et al 15. showed that there is also a dependency of the PD on the field size and the amount of modulation.…”
Section: Introductionmentioning
confidence: 99%
“…Without the flattening filter in the X‐ray beam path, the radiation output near the central axis and the dose rate at the treatment target have increased significantly, (2) which is especially beneficial to facilitate motion management during stereotactic radiosurgery (SRS) and stereotactic body radiation therapy (SBRT) 3 , 4 . In addition, the FFF photons provide dosimetric advantages, such as lower head scatter and lower out‐of‐field radiation 5 , 6 . For very high photon energies, it has been proposed that fewer neutrons can be produced with the FFF beams and thus unwanted exposure is reduced (7) .…”
Section: Introductionmentioning
confidence: 99%